VD_FINDINFO HC / 2018 / 439 vom 23. Mai 2018 - VD Tribunal cantonal (2018)
CONTRAT DE TRAVAIL, GRATIFICATION, ACCESSORIÉTÉ, RÉSERVE ET DÉCLARATION, ACCORD DE VOLONTÉS | 8 CC, 322 al. 1 CO, 322d CO, 85a LP